Southern African Liberation Movements and the global Cold War 'East' : transnational activism 1960-1990 - Fonseca, Helder Adegar, 1954- 1954- Herausgeber; Dallywater, Lena, 1983- 1983- Herausgeber; Saunders, Christopher C., 1943- 1943- Herausgeber (Dialectics of the global;, 2019)
In the global context of the Cold War, the relationship between liberation movements and Eastern European states obviously changed and transformed. Similarly, forms of (material) aid and (ideological) encouragement underwent changes over time. The articles assembled in this volume argue that the traditional Cold War geography of bi-polar competition with the United States is not sufficient to fully grasp these transformations. The question of which side of the ideological divide was more successful (or lucky) in impacting actors and societies in the global south is still relevant, yet the Cold War perspective falls short in unfolding the complex geographies of connections and the multipolarity of actions and transactions that exists until today.^